The effect of Loops and Lies game on EFL Learners' vocabulary retention in English language learning - Dava Aliv Maulana; Afifah Salwa; Halwa Halawatun Nadhroh; Cici Situmorang (Journal of Innovative and Creativity, 2026)
Vocabulary retention is one of the important aspects of learning English as a foreign language (EFL) and is very important for students of the English Language Education Study Program. However, in reality, many students are tired of maintaining vocabulary mastery in the long term so that more interesting and effective learning strategies are needed to improve their abilities. This study aims to analyze the effect of using the Loops & Lies game on vocabulary acquisition and retention of English Language Education students at the Prima Bangsa Institute Cirebon with a quantitative descriptive approach and data analysis using SmartPLS 3. The results showed that the Loops & Lies strategy had a significant effect on vocabulary acquisition of 0.562 and vocabulary retention of 0.501, while the R-square value of 0.998 indicated that the research model had very high explanatory power, so it can be concluded that the Loops & Lies game is an effective game-based learning strategy to improve vocabulary retention of EFL students in higher education.